2015
DOI: 10.1093/jpids/piv019
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin (PCT) and Kawasaki Disease: Does PCT Correlate With IVIG-Resistant Disease, Admission to the Intensive Care Unit, or Development of Coronary Artery Lesions?

Abstract: Additional research is needed to establish the sensitivity and specificity of PCT for the diagnosis of KD. PCT may be of value in predicting which children are at increased risk for IVIG-resistant disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 28 publications
4
27
0
Order By: Relevance
“…Lower serum albumin levels have previously been correlated with IVIG- unresponsiveness and CALs[33]. Our laboratory findings documented that during the acute phase of the disease serum albumin was significantly lower and PLT higher in patients with abdominal manifestations.…”
Section: Discussionsupporting
confidence: 76%
“…Lower serum albumin levels have previously been correlated with IVIG- unresponsiveness and CALs[33]. Our laboratory findings documented that during the acute phase of the disease serum albumin was significantly lower and PLT higher in patients with abdominal manifestations.…”
Section: Discussionsupporting
confidence: 76%
“…PCT has been documented as a marker of bacterial infection. However, PCT also mediates the inflammatory response; for example, high serum PCT levels have been reported in patients with Kawasaki disease [16] or with invasive trauma [4]. By contrast, the values of P-SEP do not show a similar elevation, even in patients with trauma [4].…”
Section: Discussionmentioning
confidence: 99%
“…We recruited the following laboratory data before IVIG: white blood cell (WBC) count, neutrophil count, hemoglobin (Hb), PLT count, T-Bil, albumin, AST, ALT, Na, CRP, D-dimer, brain natriuretic peptide, and FC levels. Some of these factors were previously reported to be useful in predicting unresponsiveness to IVIG [1][2][3][4][5][6][7][8][9] and can be always measured in most hospitals. According to the 2018 Japanese guide for the diagnosis and treatment of carnitine de ciency [14], low, normal, and high FC were de ned as serum FC level < 36 µmol/L , 36 µmol/L £ FC £ 74 µmol/L, and FC > 74 µmol/L, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In patients at high risks of unresponsiveness to IVIG, steroid combination therapy with IVIG is used to avoid CAL. In previous studies, several factors have been suggested as a biomarker that could predict unresponsiveness to IVIG, such as neutrophil counts, Creactive protein (CRP) and procalcitonin levels [1,2,3,4,5,6]. In Japan, Gunma, Kurume, and Osaka scores are commonly used to predict unresponsiveness to IVIG [7,8,9].…”
Section: Introductionmentioning
confidence: 99%